Art, inscriptions, and sacred space: A survey of Śaiva traditions in Southeast Asia - Lochan, Arhana (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The spread of Śaiva dharma in Southeast Asia is a vital chapter in the history of cross-cultural religious and political exchange between India and the wider region. This article traces the transmission of Śaiva ideas, rituals, and temple culture to the regions such as present-day Cambodia, Indonesia, Vietnam, and also includes examples from Laos, focusing on archaeological, inscriptional, and iconographic evidence. It investigates the royal patronage of Śaiva dharma, the regional adaptations of Indian forms, and the development of indigenous expressions of Śaiva worship. Methods: This paper is based on textual analysis, visual study of temple architecture, and secondary sources. Finding: The findings show that Śaiva practices were not simply imported from India but gradually integrated into local contexts through dynamic processes of reinterpretation, royal sponsorship, and ritual localisation. The study undertakes a regional survey of the spread and localisation of Śaiva dharma across Southeast Asia, drawing on epigraphic, architectural, and textual evidence. Conclusion: This study concludes that the spread of Śaiva dharma in Southeast Asia was not a one-way transmission from India, but a process of selective adoption, creative adaptation, and localisation. By examining evidence from Cambodia, Indonesia, Vietnam, and Laos, the research highlights how Śaiva traditions became deeply intertwined with local political authority, artistic production, and ritual life, producing uniquely regional forms of Śaiva practice that endured for centuries. Novelty/Originality of this article: The originality of this article lies in its comparative regional approach, which integrates epigraphic, iconographic, and architectural evidence to show how Śaiva dharma was reinterpreted within diverse Southeast Asian cultural settings.